Compartmental surgery for oral tongue and floor of the mouth cancer: Oncologic outcomes. Issue 1 (11th December 2018) - Piazza, Cesare; Grammatica, Alberto; Montalto, Nausica; Paderno, Alberto; Del Bon, Francesca; Nicolai, Piero
Abstract: Background: Oral tongue/floor of mouth squamous cell carcinoma (OTFMSCC) with a depth of invasion (DOI) > 10 mm involves extrinsic muscles and lingual neurovascular/lymphatic bundles. "Compartmental" hemiglossopelvectomy (CHGP) was developed to improve loco‐regional control by "en bloc" removal of tumor and its pathways of spread. Methods: We conducted a retrospective observational study on 45 CHGPs performed at a single institution for OTFMSCC with a DOI > 10 mm at CT/MR. Group A ( n  = 35) included naïve patients, and group B ( n  = 10) recurrent cancers. We evaluated 2‐year overall survival (OS), disease‐free survival (DFS), local control (LC), and loco‐regional control (LRC). Results: Two‐year OS, DFS, LC, and LRC were 80%, 91%, 100%, and 94% for group A, and 27%, 26%, 67%, and 36% for group B, respectively. Salvage surgery and positive margins were significantly associated with worse prognosis. Conclusion: CHGP is a reliable oncologic approach in primary surgery for advanced OTFMSCC. In recurrent cancers, survival remains poor.